High-Power Emission via Large-Area VCSELs With Single High-Order Mode Operation - Valerio Torrelli; Alberto Gullino; Alberto Tibaldi; Francesco Bertazzi; Michele Goano; Pierluigi Debernardi (IEEE Photonics Journal)
In this work we investigate patterned large-active area AlGaAs vertical-cavity surface-emitting lasers (VCSELs) targeting high-power single-transverse-mode emission. As a first step, our in-house 3D electromagnetic vectorial mode solver VELMS is validated against preliminary experimental data. Then, VELMS is applied to implement single-mode operation on VCSELs featuring large-area rectangular oxide apertures. A comparative appraisal of different mode selection strategies based on patterning the outcoupling facet of the device is presented, providing a number of alternatives for a broad audience of technologists.